Fighting terror after Napoleon: how Europe became secure after 1815 - Graaf, Beatrice de (Cambridge University Press, 2020)
Introduction : Napoleon's frustration -- Providence in Paris -- Balancing a climate of distress -- "A moderate occupation" -- "Fausses nouvelles" and "black lists." The Allied struggle against "armed Jacobinism" -- Fighting "terroristes" together. Towards a "European police directorate"? -- The price of security -- Fortress Europe. Constructing the "Wellington Barrier" -- Beyond Europe -- Conclusion.